Production of Activated Carbon from Watermelon Peels for Treatment of River Water - Bethany Albert Charles; Eshwary Thanabalan; Ahmad Nordin, Norain; Nuramirah Juma’at (Multidisciplinary Applied Research and Innovation, 2024)
Today, numerous research groups have been drawn to the production of low-cost activated carbon from agricultural waste materials, such as fruit wastes which is abundant and renewable. The utilization of agricultural waste, such as from the watermelon peels, presents an intriguing alternative due to its potential for conversion into activated carbon. Hence, in this study, watermelon peels were used to produce activated carbon (AC) for the treatment of river water. The watermelon peels were washed and dried for 24 hours at 60℃. Then, the watermelon peels were carbonized at 300℃ for 60 minutes and chemically activated in 1.0 M of 24 for 24 hours. The ash, moisture, volatile carbon, and fixed carbon content were examined to evaluate the quality of activated carbon. Besides, the surface morphology were analysed using scanning electron microscopy (SEM) at ×500 magnification. By measuring BOD, turbidity, and pH with various activated carbon masses—0.5g, 1.0g, 1.5g, 2.0g, and 2.5g—the effectiveness of the material in treating Muar River water samples were measured. Results demonstrated, an increase of the amount of AC, gives an increase in reduction of BOD (24.79-0.54 mg/L), turbidity (0.70-0.00 NTU) and pH (6.5-7.5 pH) of the treated Muar River water. In addition, SEM image appeared spongy indicating the development of pores thus increasing the adsorption capacity. Therefore, this study established the feasibility of employing watermelon peels as a cost-effective and efficient raw material to produce activated carbon for the treatment of river water.